Antibacterial thermoplastic starch/sepiolite bio-nanocomposite films: Effects of plasticizer type and starch source - Cokkuvvetli, Ayse Tugce; Deniz, Sennur (SAGE PUBLICATIONS LTD, 2025)
The use of starch-based films as an alternative food packaging has gained prominence as part of efforts to ensure sustainability and manage post-user waste, aligning with European regulations and broader global sustainability goals. In this study, Thermoplastic starch (TPS) bio-nanocomposite hybrid films were developed by incorporating high purity sepiolite (HPS) and Turkish oregano extract (OE) as reinforcement and antimicrobial additives, respectively. The interactive effects of four experimental variables (temperature, time, plasticizer type, and ratio) on the mechanical characteristics of corn and potato starch-based films were evaluated using Box-Behnken response surface methodology. A three-level, three-factor Box-Behnken design was utilized to investigate the effects of the experimental variables on tensile strength (TS), elongation at break (EB), and E-modulus (EM) of the starch-based films. The potato-based TPS films using sorbitol rather than glycerol exhibited better mechanical properties than corn starch-based TPS films under the optimized experimental parameters of 70 degrees C gelatinization temperature, 60 minutes gelatinization time, and 40% sorbitol plasticizer. The addition of 3% HPS slightly enhanced the mechanical (TS: 26.0 MPa, EB:11.3%, and EM:1817 MPa) and oxygen permeability characteristics (OTR: 25 cc/m2.day) of the potato-based bio-nanocomposite films. The hybrid films prepared with the addition of OE provided >99.7% antibacterial resistance to E. coli and S. aureus bacteria (in accordance with ASTM D3985). These findings suggest that starch-based hybrid films offer a promising approach to address both environmental and food safety concerns, raising the prospect of using such films as innovative active packaging materials in the future.
Keywords: Thermoplastic starch; plasticizer; high purity sepiolite; Turkish oregano extract; active packaging; OPTICAL-PROPERTIES; ESSENTIAL OILS; BARRIER; MORPHOLOGY; GLYCEROL; BLENDS; ACID; Materials Science